The concept and the model of territorial cohesion – geographical aspect - Grižančič, Sabina (Journal for Geography, 2014)
In October 2008, European Commission published the Green Paper on Territorial Cohesion which opened an extensive discussion about the concept of territorial cohesion which is, together with economic and social cohesion, the main objective of European Union. Although many experts warn that the implementation of territorial cohesion (TC) in policy without clear definitions and indicators cannot be successful, the concept of territorial cohesion remains still unclear. The article provides an outline of an extensive study of the concept of territorial cohesion. The study dealt with the geographical definition of territorial cohesion (spatial cohesion), identifying indicators and building a model for measuring it. At the end the paper provides a case study of measuring TC at NUTS 3 region of Slovenia.